Does d-cycloserine facilitate the effects of homework compliance on social anxiety symptom reduction?. (January 2018) - Roque, Andres D.; Rosenfield, David; Smits, Jasper A.J.; Simon, Naomi; Otto, Michael W.; Marques, Luana; Pollack, Mark H.; Hofmann, Stefan G.; Meuret, Alicia E.
Highlights: Relationship between homework compliance, DCS, and treatment outcome was examined. 169 patients with generalized social anxiety disorder received 12-sessions of CBT. DCS or pill- placebo was randomly assigned to patients during exposure sessions. Homework compliance was positively associated with reductions in anxiety symptoms. DCS did not moderate the relationship between homework compliance and outcome. Abstract: Background: Prior studies examining the effect ofd -cycloserine (DCS) on homework compliance and outcome in cognitive-behavior therapy (CBT) have yielded mixed results. The aim of this study was to investigate whether DCS facilitates the effects of homework compliance on symptom reduction in a large-scale study for social anxiety disorder (SAD). Methods: 169 participants with generalized SAD received DCS or pill placebo during 12-session exposure-based group CBT. Improvements in social anxiety were assessed by independent raters at each session using the Liebowitz social anxiety scale (LSAS). Results: Controlling for LSAS at the previous session, and irrespective of treatment condition, greater homework compliance in the week prior related to lower LSAS at the next session. However, DCS did not moderate the effect of homework compliance and LSAS, LSAS on homework compliance, or the overall augmenting effect of DCS on homework compliance. Furthermore, LSAS levels were not predictive of homework compliance in the following week. Conclusion: The findings support the general benefits of homework compliance on outcome, but not a DCS-augmenting effect. The comparably small number of DCS-enhanced sessions in this study could be one reason for the failure to find a facilitating effect of DCS.